Manufacture of Low-Grade Zeolites from Fly Ash for Fertiliser Applications - Fansuri, Hamzah; Pritchard, Deborah; Zhang, Dong-Ke (QCAT Technology Transfer Centre, Technology Court, 2008)
Conversion of fly ash into zeolite is a preferred way to improve fly ash utilisation by value-adding. In this work, fly ash was converted into zeolite using an improved hydrothermal method with optimised H2O/Al molar ratio. It was found that the optimum ratio is 57.4 where the main zeolite product is analcime. The zeolite, in the forms of both K-and Na-zeolite, was subjected to trials of plants (canola, spinach and wheat) grown in pots using two types of soils, namely pale deep sand (Bassendean sand) and deep sandy gravel (Collie soil). When planted in Bassendean sand, spinach and wheat grew better at 1 and 2 wt% of K and Na-zeolite additions while canola only grew better at 1 wt% K-zeolite addition. When the zeolites were added to a more fertile Collie soil, there is an apparent beneficial effect on canola, spinach and wheat at all 3 levels of additions of both types of zeolite. Cadmium and Mercury were detected on the dried shoots of canola, spinach and wheat planted on both soils without zeolite addition. However their concentrations were still within FAO and WHO recommended levels. The Cadmium and Mercury level decreases as higher percentage of zeolites were added to the soils, which is evidently due to that the zeolites retain the heavy metals firmly within its structure.